The Message of Peace in the Poem Nuhibbu Al-Bilad by Anis Chouchene: (Roland Barthes’s Semiotic Analysis) - Ahsan Rasyid, Muhammad (Universitas Ahmad Dahlan, 2025)
This study aims to reveal the message of peace embedded in Nuhibbu al-Bilad, a poem by Anis Chouchene, using Roland Barthes’s semiotic analysis. The poem holds significant relevance in addressing humanitarian issues in post-Arab Spring Tunisia. The research employs a descriptive qualitative method, with the primary data drawn from the poem’s text and analyzed through Barthes’s three layers of meaning: denotation, connotation, and myth. The findings show that, at the denotative level, the poem portrays patriotism as the foundation for stability after political upheaval. At the connotative level, the text evokes themes of reconciliation, tolerance, and national reconstruction. At the mythic level, the poem constructs a narrative of harmonious national identity and a collective longing for peace. It also functions as a critique of authoritarian regimes and structural inequality in Tunisia. The poem reflects the poet’s call for justice and unity through a complex network of symbolic language. In conclusion, Nuhibbu al-Bilad not only conveys a profound message of peace but also articulates the collective aspirations of the Tunisian people for a better future through a meaningful system of signs. This study contributes to the fields of modern Arabic literature and peace studies by demonstrating how poetry serves as a medium of ideological expression, social critique, and the construction of national discourse in the context of socio-political transformation.